(untitled) (International Journal of Engineering and Computer Science, 2015)
Internet communication has become the essential part of the infrastructure of today’s world. The information communicated in various forms and this information is used in many applications which are in a secrete format. Security is one of the most important factors for transferring different types of important documents. Internet is one of the most important media which is used to transfer documents. This is used in bank transfers, email communications, credit card purchases on large number of daily email and military application. But in reality the internet is not a secure form. So we are suggesting VC that is visual cryptography method which is simple, fast and provide security while sharing secretes documents over the internet. These documents are presented in a bit map format file, and extend it into two or more encoded file shares which can be transferred to the receiver in a cover image using BPCS that is Bit Plane Complexity Segmentation technology through electronic mail. The Bit Plane Complexity Segmentation allows hiding large secret information into cover image. This cover images are selected for analysis and according to the threshold value it will increase the complexity of each segment to verify the changes occurred in the original image. And data will be stored at higher complexity. Steganography is technique of data hiding. Steganography is a technique in which secret data is hidden into vessel image. All other techniques have limited data hiding Capacity and other technique can hide up to 15% of data amount of vessel image. But hiding capacity of steganographic technique is up to 50 –60%. This technique is called Bit Plane Complexity Segmentation (BPCS) Steganography. Therefore, the final image can be obtained only when the number of shares is combined together at receiving side. Thus a combined use of VC and BPCS technology provides data security to all forms of documents during transfer over internet.